Severe hypernatremia in children after surgical resection of hepatic echinococcosis: a rare and potentially fatal complication - Kewei Li; Yijun Liu; Xiaolong Xie; Rongxing Zhou; Bo Xiang (BMC, 2021)
Abstract Background Using effective scolicidal agents intraoperatively is essential to lessen the recurrence rate of hepatic echinococcosis. However, severe hypernatremia may occur after hypertonic saline (HS) has been applied as the scolicidal agent. The aim of this study is to report on pediatric patients with severe hypernatremia after hepatic echinococcus surgery. Methods Patients who presented to West China Hospital between January 2010 and February 2017 were retrospectively analyzed. Children under 16 years with echinococcosis treated by resection were included in the study. Results A total of 26 children were enrolled in this study, including 16 boys and 10 girls with a median age of 8 (2-16). 24 (92.3 %) cases were cystic echinococcosis (CE) and two (7.7 %) were alveolar echinococcosis (AE). According to Clavien-Dindo classification of surgical complications, the complication rate of all 26 patients was 19.2 %, among which three cases belonged to Grade I, one to Grade III b and 1 to Grade IV. Two children encountered severe hypernatremia (sodium: 155.3 mmol/L and 190.0mmol/L). Data showed classic clinical features of severe hypernatremia: profound and persistent bradycardia, hypotension and coma. After treatment, they recovered well without any neurologic sequelae. All patients were followed up regularly for a median time of 38 months (range 4-89 months); the overall disease-free survival was 100.0 %. Conclusions HS irrigation of intra-abdominal echinococcosis may cause acute hypernatremia and severe consequences. Diagnostic suspicion and early intervention are vital tools for avoiding morbidity and mortality.